Respostas
respondido por:
1
Boa tarde
a)
(3 x) (4 - 1)
>
(2 1) (1 2)
3 - 2x > 8 + 1
3 - 2x > 9
2x < -6
x < -3
b)
2x 3 2 2x 3
1 x 1 x 1
0 1 1 0 1
det = 2x² + 2x - 2x - 3x = 0
2x² - 3x = 0
x*(2x - 3) = 0
x1 = 0
x2 = 3/2
a)
(3 x) (4 - 1)
>
(2 1) (1 2)
3 - 2x > 8 + 1
3 - 2x > 9
2x < -6
x < -3
b)
2x 3 2 2x 3
1 x 1 x 1
0 1 1 0 1
det = 2x² + 2x - 2x - 3x = 0
2x² - 3x = 0
x*(2x - 3) = 0
x1 = 0
x2 = 3/2
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás